Managing Creativity at Shanghai Tang - CHUA, Roy (Institutional Knowledge at Singapore Management University, 2009)
Shanghai Tang is a luxury brand that focuses on Chinese-inspired fashion, accessories, and home decoration products. In Fall 2008, amidst a growing global economic crisis, Raphael Ie Masne, executive chairman of Shanghai Tang, had to decide what to do with the recently vacant creative director position. Did Shanghai Tang need to hire a new creative director at this uncertain economic time? Or could he take on the role of the creative director himself? In addition, Ie Masne had to grapple with balancing the perennial tensions between business imperatives and the creative aspirations of his designers. How could he better manage employees who see themselves as artists?